Análise de ocorrências dos impactos pluviais na área urbana de Rio Claro (SP) - Lopes, Leiliane Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The Urbanization is a notable process in our society, being part of it since around 3500 BC in Mesopotamia, currently Iraq area. Since the Industrial Revolution, cities had a significant increase in their growth and began to concentrate increasingly labor and capital. Brazil, despite having had a late industrialization, also had a high population growth in cities, especially in the XVIII century, which were not provided with any kind of planning that targets the ordering and implementation of the urban essential apparatus. Therefore, Brazilian cities started to exhibit countless structural and environmental problems. Associated with inadequate infrastructure, the modifications in the urban atmosphere, like increased heat, air pollution and increased rainfall and storm frequency, cause different types of impacts in cities. Among the most worrisome are those from the intense rain, which cause human and material damage. The city of Rio Claro (SP) can be considered an example of this reality. Thereby, the objective of this study was to analyze the impacts on the population originated from rainfall in the urban area during the period 2005-2010, by the mapping of events and analysis of the active atmospheric systems. The information of the events were collected in the Fire Department and the Press and the synoptic maps were obtained in the library of INPE, in Cachoeira Paulista (SP) and in the site of the Navy of Brazil. The data showed that among 247 occurrences, during the six years, 233 occurred in the spring-summer period. Moreover, after finalizing the maps, it was found the locations considered critical regarding the frequency of occurrences, as: Visconde do Rio Claro Avenue and central area of the city, both with a total of 23 occurrences; Jardim Inocoop, with 20; Tancredo Neves Avenue, with 12 and Vila Paulista, with 10 occurrences. Through the graphs, it was found that the most recurrent atmospheric system, during the studied period, is...

A urbanização é um processo marcante em nossa sociedade, presente desde por volta de 3.500 A.C, na Mesopotâmia, área do atual Iraque. A partir da Revolução Industrial, as cidades tiverem um expressivo aumento no seu crescimento e passaram a concentrar cada vez mais força de trabalho e capital. O Brasil, apesar de ter tido uma industrialização tardia, também teve um elevado aumento populacional nas cidades, principalmente no século XVIII, as quais não foram providas de nenhum tipo de planejamento que visasse o seu ordenamento e a implementação dos aparelhos urbanos essenciais. Logo, as cidades brasileiras passaram a apresentar incontáveis problemas estruturais e ambientais. Associadas à inadequada infraestrutura, as alterações da atmosfera urbana, as quais estão relacionadas ao aumento do calor, a poluição do ar e, em especial destaque, ao aumento das precipitações e da frequência das tempestades, ocasionam diversos tipos de impactos nas cidades. Dentre os mais preocupantes, estão os oriundos da ação pluvial intensa, que acarretam prejuízos materiais e humanos. A cidade de Rio Claro (SP) pode ser considerada um exemplo dessa realidade. Desse modo, o objetivo do presente trabalho foi analisar os impactos à população oriundos das precipitações pluviais na área urbana, durante o período de 2005 a 2010, por meio do mapeamento das ocorrências e da análise dos sistemas atmosféricos atuantes. As informações referentes às ocorrências foram coletadas no Corpo de Bombeiros e na Imprensa, já as cartas sinóticas foram obtidas na biblioteca do INPE, em Cachoeira Paulista (SP) e no site da Marinha do Brasil. Os dados mostraram que dentre 247 ocorrências, nos seis anos, 233 aconteceram no período primavera-verão. Além disso, após a realização dos mapeamentos, foi possível verificar as localidades consideradas como pontos críticos no que diz respeito à frequência das ocorrências, sendo elas: a Av. Visconde...
Keywords: Climatologia; Climatologia geográfica; Planejamento urbano; Urbanização; Chuvas - 2005-2010; Rio Claro (SP)